The global research landscape and future trends in healthcare Total Quality Management - Zhiyuan Hu; Richard Szewei Wang; Xiaoping Qin; Yu-Ni Huang; Lin Li; Herng-Chia Chiu; Yuanli Liu; Bing-Long Wang (BMC, 2024)
Abstract Total Quality Management (TQM) is instrumental in augmenting the quality and efficacy of healthcare service delivery, but a comprehensive evaluation of present and evolving TQM research trends within healthcare research articles is notably absent. This study provides an insightful view into the prevailing international scenarios and upcoming research frontiers in healthcare TQM research field, utilizing bibliometric mapping through VOSviewer. Drawing data from 360 publications in the Web of Science core citation database, it delineates a steady growth in the field over the last 30 years. Research outputs span 51 countries and regions, with notable contributions from the United States, United Kingdom, Netherlands, and Italy. The top five research institutions and numerous authors predominantly hail from the United States. Key keywords in near years encompass healthcare safety, healthcare quality assurance, quality indicators, and the application of Six Sigma management principles. This exploration serves as a pivotal reference for understanding the global research landscape and future trends in healthcare TQM, particularly in guaranteeing quality and safety. Future scientific endeavors will build upon these focus areas, exploring and connecting research gaps in more specialized fields.